An incongruous occurrence: rare case of a huge sinonasal neurofibroma - Malhotra, Vikas; Sethi, Deepika; Mahajan, Nidhi; Chatterjee, Moudipa; Aggarwal, Nitish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Neurofibromas (NF) are benign peripheral nerve sheath tumors that arise from schwann cells and intraneural fibroblasts. Solitary NF are extremely rare with only a few reported cases in the literature that involve the nasal cavity and paranasal sinuses. Due to its slow growth and the non-specific nature of the symptoms, its clinical presentation and diagnosis is often delayed. Here we present a case of a 65 year old female with left sinonasal neurofibroma which was surgically managed in our department successfully. It was 9.5 cm in greatest dimension and weighed 380 gm which is the largest amongst the available published reports that we could find.